Variability in Myth-Ritual Content in the Australian Aboriginal Fire Ceremonies - Szyjewski, Andrzej (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2016)
The paper’s aim is to reconsider mechanisms of change in mythical content within Australian Aboriginal traditions. Despite Jack Goody’s claim, myths do not change arbitrarily as the “free-floating use of the creative imagination”. An overview of the mythical and ritualcomplexes related to fire ceremonies in Australia shows that the content volatility is strongly limited due to the requirements of the syntagm, as well as to dominant trends of metaphorization, and to the model of the world in the form of a cosmological system. Fire ceremonies, being a common part of initiation rituals, tend to combine symbolic wounds, fire, Milky Way, Rainbow Serpent, demonic cannibal and male/female opposition within mythic narratives. Such imagery appears unchangeable regardless of changes in mythical content or variability in rites. An indigenous Australian model of the world is based on oppositions between water/fire and dry season/rainy season, and switching between them requires the myth of cosmic catastrophe.astly, all ttiation narrative variants assume the bodily transformations of numerous initiands, mostly in the form of destruction and regeneration.
Keywords: Australian Aborigines; initiation; fire ceremonies; myth; mythic metaphor; mythic transformation; orality; ritual